1965
DOI: 10.1126/science.149.3681.310
|View full text |Cite
|
Sign up to set email alerts
|

Interferon-Like Virus-Inhibitor Induced in Human Leukocytes by Phytohemagglutinin

Abstract: Phytohemagglutinin, an extract of the kidney bean, Phaseolus vulgaris, induces in human leukocyte cultures an inhibitor of the cytopathic effects of Sindbis virus. The physicochemical and biological properties of this virus-inhibitor are similar to those of interferon induced by Newcastle disease virus, except for an instability at pH 2 and 10 and at 56 degrees C.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
256
1
8

Year Published

1970
1970
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 645 publications
(276 citation statements)
references
References 11 publications
6
256
1
8
Order By: Relevance
“…It is conceivable that the blastic transformation of the lymphocyte in culture is associated with a derepression of a genetic locus normally expressed in other cell types. Derepression has been suggested as an explanation for the synthesis of interferon both in lymphoblast cell lines (16) and in PHA-stimulated lymphocytes (17) and for the production of multiple types of immunoglobulins by cloned lymphocytes in long-term culture (18). Also, in the case of malate dehydrogenase, there is evidence that a specific isoenzyme can be selectively synthesized in PHA-stimulated lymphocytes (19) …”
Section: Discussionmentioning
confidence: 99%
“…It is conceivable that the blastic transformation of the lymphocyte in culture is associated with a derepression of a genetic locus normally expressed in other cell types. Derepression has been suggested as an explanation for the synthesis of interferon both in lymphoblast cell lines (16) and in PHA-stimulated lymphocytes (17) and for the production of multiple types of immunoglobulins by cloned lymphocytes in long-term culture (18). Also, in the case of malate dehydrogenase, there is evidence that a specific isoenzyme can be selectively synthesized in PHA-stimulated lymphocytes (19) …”
Section: Discussionmentioning
confidence: 99%
“…In mammals, IFN is classified into type-I IFN (α, β, ε, δ, τ and ω), type-II IFN (γ) and type-III IFN (λ) based on their differences in primary structure, serology and their most likely time of evolutionary divergence 8,9,10 . Interferon-gamma (IFN-γ) is a pleiotropic proinflammatory and antiviral cytokine, which was initially identified in PHA-activated mammalian lymphocyte supernatants 11 . It was demonstrated that IFN-γ is a central participant in host resistance to various infections by using IFN-γ knockout mice infected with Leishmania major 12 , Listeria monocytogenes 13 and Mycobacteria 14 .…”
Section: Introductionmentioning
confidence: 99%
“…The synthesis of interferon from lymphocytes can also be induced by immune stimulation (bacterial [16] and viral antigens [17][18][19], alloantigens [20]), anti-lymphocyte sera (21), and mitogenic lectins (22).…”
mentioning
confidence: 99%